Rare Coexistence of SLC6A9 and TOR1A Gene Mutations in a Neonate Presenting with Hereditary Hyperekplexia and Arthrogryposis Multiplex Congenita: A Case Report with Review of Literature - Bhavya Patel; Shwetal Bhatt; Vaishali Chanpura (Wolters Kluwer Medknow Publications, 2023)
Background: Neonatal hyperekplexia is a rare nonepileptiform disorder characterized by an exaggerated startle reflex associated with generalized hypertonia. We report a newborn with mutation in the glycinergic inhibition pathway resulting in hyperekplexia, associated with features of arthrogryposis multiplex congenita. Clinical Description: A 3-day-old newborn born at term vaginally cried immediately after birth and presented with lethargy, poor cry, and abnormal clonic movements of all four limbs. On examination, there was hyperreflexia and hypertonia in all four limbs along with dislocation of the right knee joint. Blood investigations, including tandem mass spectrometry, serum ammonia, serum, and cerebrospinal fluid glycine levels, were normal, ruling out inborn errors of metabolism responsible for hyperekplexia and arthrogryposis. The magnetic resonance imaging (MRI) brain and electroencephalogram were normal, while the MRI spine showed kyphosis. The genetic evaluation showed heterozygous missense mutation in exon 6 of the SLC6A9 gene and homozygous mutation in the TOR1A gene, which explained the hyperekplexia and the arthrogryposis multiplex congenita. Management and Outcome: The patient received supportive care. Oral clonazepam and levetiracetam were started in view of hypertonia and clonic spasms. Feeding was given by intragastric tube as he had poor suck-swallow coordination. Conclusions: This case highlights an interesting and extremely rare combination of hereditary hyperekplexia and arthrogryposis multiplex congenita existing together in the same patient, confirmed by the corroborating genetic mutations. Awareness of such conditions among pediatricians is essential to order appropriate genetic evaluations and treatment accordingly.